2021
DOI: 10.21001/sintagma.2021.33.05
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic errors in the biomedical domain: Towards an error typology for Spanish

Abstract: Linguistic errors in the biomedical domain: Towards an error typology for Spanish. The objective of this work is the analysis of errors contained in a corpus of medical reports in natural language and the design of a typology of errors, as there was no systematic review on verification and correction of errors in clinical documentation in Spanish. In the development of automatic detection and correction systems, it is of great interest to delve into the nature of the linguistic errors that occur in clinical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Studies on types of errors in Spanish clinical reports have been recently carried out; these works have focused on spelling errors and non-word errors. For instance, in López-Hernández et al (2021), a corpus of emergency medicine was analyzed and the authors concluded that the length of the words is a variable that influences the frequency of errors. This paper also highlights the significant frequency with which the prefixes are separated from the lexical base which they complement, and the lack of consistency in the use of abbreviations.…”
Section: Error Analysis and Automatic Correction In The Medical Domainmentioning
confidence: 99%
“…Studies on types of errors in Spanish clinical reports have been recently carried out; these works have focused on spelling errors and non-word errors. For instance, in López-Hernández et al (2021), a corpus of emergency medicine was analyzed and the authors concluded that the length of the words is a variable that influences the frequency of errors. This paper also highlights the significant frequency with which the prefixes are separated from the lexical base which they complement, and the lack of consistency in the use of abbreviations.…”
Section: Error Analysis and Automatic Correction In The Medical Domainmentioning
confidence: 99%